Practice of lateral dominance: an early evaluation strategy in children from the rural area of Puno - Zela-Payi, Nelly Olga; Ticona-Arapa, Haydee Clady (International Journal of Evaluation and Research in Education (IJERE), 2025)
The purpose of this study was to investigate the practice of lateral dominance as an early evaluation strategy in children from the rural area of Puno, Peru. Early assessment of lateral dominance is crucial for understanding a child’s cognitive and motor development. This study focused on children attending a school for children with learning disabilities in the rural Initial Educational Institution Camacani within the Local Educational Management Unit of Puno, located in the southern region of the Province of Puno, under the jurisdiction of the Platería District. A total of 100 children (50 boys and 50 girls), aged 5 years, were selected for the study. The research was descriptive-quantitative in nature, aimed at evaluating the dominance of four dimensions—hands, feet, ears, and eyes—using the Harris test. The findings revealed that lateral dominance in both boys and girls was characterized by poorly affirmed laterality in 60% of the cases and crossed laterality in 40%. This suggests that at the age of 5 years, the children were still in the developmental stage of lateralization, with no clear dominance of the left or right hemisphere. Based on the results, it was concluded that lateral dominance in these children was not yet fully established. Furthermore, the study emphasized the importance of incorporating psychomotor activities during early childhood development to promote the continuous improvement of laterality, motor skills, and spatial orientation.